Implementation of Manokwari Regency DPRD Duties Regarding Supervision of Regional Government Performance Based on Law Number 23 of 2014 concerning Regional Government - Irfan Christianto; Filep Wamafma; Atang Suryana (Yayasan Ilomata, 2023)
Law no. 23 of 2014 concerning Regional Government provides a legal basis for the Regional People's Representative Council (DPRD) in supervising the performance of regional government. The Manokwari DPRD, as one of the legislative institutions at the regional level, has an important role in carrying out this supervisory task. This research aims to examine the implementation of the Manokwari DPRD's duties in monitoring regional government performance based on Law no. 23 of 2014. The research method used is descriptive analysis with a qualitative approach. Data was obtained through interviews with members of the Manokwari DPRD, document analysis, and direct observation of the Manokwari DPRD's work processes related to monitoring regional government performance. The research results show that the Manokwari DPRD has carried out its supervisory duties in accordance with the provisions of Law no. 23 of 2014. They supervise regional government performance through a number of mechanisms, such as commission meetings, plenary meetings, and examination of regional heads' accountability reports. They also play an active role in monitoring the use of regional budgets and evaluating regional government programs. However, there are several challenges in carrying out the supervisory duties of the Manokwari DPRD. One of them is limited resources, both in terms of manpower and budget. Apart from that, sometimes there are political obstacles that affect the independence of the DPRD in carrying out its supervisory function. Some DPRD members also face obstacles in accessing information needed for supervision. In the context of monitoring regional government performance, the Manokwari DPRD has great potential to increase accountability and transparency of regional government. To overcome the challenges faced, efforts are needed to strengthen the capacity of DPRD members, increase budget allocations, and ensure DPRD independence in carrying out supervisory duties. Apart from that, good cooperation between the DPRD and regional governments in providing access to the necessary information is also important. In conclusion, the implementation of the Manokwari DPRD's duties in monitoring regional government performance is based on Law no. 23 of 2014 has been running well, although there are still several challenges that need to be overcome. With the right efforts, the Manokwari DPRD can play a more effective role in increasing accountability and transparency of local government and improving the quality of public services for the people of Manokwari.